2020
DOI: 10.4314/ejhs.v30i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Peptic Ulcer Disease in a Tertiary Hospital, Addis Ababa, Ethiopia: Five Year Retrospective Study

Abstract: BACKGROUND: Peptic ulcer perforation is one of the two major acute complications of peptic ulcer disease with significant morbidity and mortality.METHODS: Institution based retrospective review was done to determine patient presentation, management and postoperative complications of perforated peptic ulcer disease (PPUD) at a tertiary hospital in Addis Ababa, Ethiopia. Patients operated on from January 2013 to December 2017 were included. Univalent analysis was used to determine the influence of patient and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
(25 reference statements)
2
4
0
Order By: Relevance
“…The study has revealed that there is a high male predominance in having perforated peptic ulcer disease (3.7:1), which is consistent with several other studies conducted in Africa (5,8,20) but in contrary to Western setups, where it is a disease of elderly women with comorbidities (9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study has revealed that there is a high male predominance in having perforated peptic ulcer disease (3.7:1), which is consistent with several other studies conducted in Africa (5,8,20) but in contrary to Western setups, where it is a disease of elderly women with comorbidities (9).…”
Section: Discussionsupporting
confidence: 90%
“…Graham's omental patch of the perforations with either a pedicled omental patch or a free graft of omentum was the procedure performed for the majority of patients in this study. The mortality rate in this study was found to be 4.25% which is comparable with a study conducted in central Ethiopia 6.6% (20), but lower than the ndings of several other studies done in Tanzania (10.7%), Black Lion Hospital (BLH), Ethiopia (19%) and India (14%) (3,8,14). Relatively younger patients and a lower prevalence of comorbid illness in this study can explain this nding of a lower mortality rate.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we found that before the pandemic, PPU were predominantly male. Previous research before the pandemic period has also shown males were more at risk of developing a complicated peptic ulcer, especially in a developing country [11,12] . During the pandemic, PPU were predominantly female.…”
Section: Discussionmentioning
confidence: 92%
“…The clinical picture may be less clear in the obese, the immunocompromised, patients on steroids, patients with a reduced level of consciousness, the elderly, and children. In these situations, the clinical history and examination may be non-specific prompting additional imaging and laboratory studies to rule out differential diagnoses' The presence of gas under the diaphragm on plain abdominal erect X-ray is diagnostic in 75% of the cases [4,6,7].…”
Section: Introductionmentioning
confidence: 99%